The Effect of Brand Image, Word Of Mouth, and Price Perception on Luwak White Koffie Purchase Decisions in Makassar City - Andi Risnayani; Anwar Ramli; Nurul Fadilah Aswar; Muhammad Ilham Wardhana Haeruddin; Rahmat Riwayat Abadi (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of Brand Image, Word of Mouth, and Price Perception on Purchase Decisions of Luwak White Koffie products in Makassar City. This research used a quantitative approach with an explanatory research type and causal design. The population in this study consisted of all consumers of Luwak White Koffie in Makassar City who had purchased the product. The sampling technique used was non-probability sampling with a purposive sampling approach, involving 120 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of the Statistical Package for the Social Sciences (SPSS). The results showed that Brand Image, Word of Mouth, and Price Perception partially had a positive and significant effect on Purchase Decisions. Simultaneously, Brand Image, Word of Mouth, and Price Perception also had a positive and significant effect on Purchase Decisions of Luwak White Koffie products in Makassar City